The Relationship between Burnout and Learning Motivation in Full-day School Students at SMPN 34 Padang - Mutia Helfajrin; Zadrian Ardi (Universitas Negeri Padang, 2020)
This research was conducted because it saw problems that occur in full day school students who experience boredom of learning so that it affects the students' motivation to learn low. This study aims to examine the relationship of learning motivation with full day student learning saturation. The number of samples was 222 students of 34 Padang Junior High Schools selected by using simple random sampling. The instrument used was a Likert scale model, as well as data processed using SPSS version 19 '. The results obtained from this study are that there is a significant negative relationship between learning motivation and learning saturation with a correlation coefficient of -0.512 which is at a significance level of 0.000 with a strong enough category. This means that the higher the motivation to learn, the lower the saturation of student learning. With this finding it is hoped that counselors or counseling teachers can provide guidance and counseling services such as information services, individual counseling services, group guidance services, and group counseling services. To increase learning motivation and to reduce boredom in full day school students.